Developing a quality measure to assess use of antibiotic medications for respiratory conditions - Brandi L. Melville; Taylor Musser; Ezra Fishman; Danielle Rainis; Sepheen C. Byron (Antimicrobial Stewardship & Healthcare Epidemiology, 2023)
Abstract